2021
DOI: 10.1177/14680874211065237
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Bayesian optimization for predicting borderline knock

Abstract: Engine knock is an undesirable combustion that could damage the engine mechanically. On the other hand, it is often desired to operate the engine close to its borderline knock limit to optimize combustion efficiency. Traditionally, borderline knock limit is detected by sweeping tests of related control parameters for the worst knock, which is expensive and time consuming, and also, the detected borderline knock limit is often used as a feedforward control without considering its stochastic characteristics with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…With all these, the model has three unknowns to be solved for the Kriging model and they are scalar σ , parameter vector β and θ . They are determined by maximizing the likelihood function (see Tang et al 4 for details) over the observed points. Accordingly, the predicted mean μ and mean square error s 2 for y ( x ) are predicted by the following equations:…”
Section: Offline Trained Surrogate Model Through Bayesian Optimizatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…With all these, the model has three unknowns to be solved for the Kriging model and they are scalar σ , parameter vector β and θ . They are determined by maximizing the likelihood function (see Tang et al 4 for details) over the observed points. Accordingly, the predicted mean μ and mean square error s 2 for y ( x ) are predicted by the following equations:…”
Section: Offline Trained Surrogate Model Through Bayesian Optimizatio...mentioning
confidence: 99%
“…3 The knock combustion is affected by many aspects such as spark timing, trapped gas composition and temperature as a result of gas exchange process due to EGR, intake and exhaust valve timings. 4 In order to avoid undesired knock and achieve the best possible engine efficiency, the control parameters (such as spark timing, EGR and valve timings, etc.) need to be optimized through an extensive calibration process.…”
Section: Introductionmentioning
confidence: 99%
“…However, our early study on knock stochastic properties 10 shows that the knock intensity probability density function (PDF) is not a symmetric Gaussian random process but has a log-nominal distribution, which was also verified by other researchers. 13 Thus a distribution conversion 11 is necessary to make it possible to implement the system identification algorithm. On the other hand, the fluctuation and absolute amplitude of δ temperature have a much larger range than these of the knock intensity; see Figures 10 and 12.…”
Section: System Identification and Model Verificationmentioning
confidence: 99%
“…The overall knock control architecture is shown below in Figure 1. The offline trained stochastic surrogate model 11 is updated in real-time and provides the baseline spark timing to the engine controller. This paper focuses on the δ spark timing compensation, which is the red path shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The approach has been validated in easing the computational burden for various problems ranging from parameter calibration and control design. References [16], [17], [18], [19], [20], [21], [22] implemented the Bayesian optimization framework in automotive domain for performing the engine calibration. Apart from automotive applications, the Bayesian optimization approach has also been successfully implemented in other applications such as analog/rf circuit design [23], groundwater reactive transport model [24], actuator modeling [25], and designing natural-gas liquefaction plant [26].…”
Section: Introductionmentioning
confidence: 99%